Comparative Transcriptome Analysis Reveals a Tissue-Specific Pathway Involved in Nitrogen Utilization Between Genotypes with Different Nitrogen Use Efficiencies in Tea Plants (Camellia sinensis) - Min Wang; Kangwei Sun; Xujun Qin; Shuting Gong; Zhipeng Li; Kai Fan (Agronomy)
Nitrogen (N) is a key nutrient which affects plant development and quality formation for tea plants. Notable genetic variation in nitrogen use efficiency (NUE) has been reported among different genotypes of Camellia sinensis. However, the molecular mechanisms underlying these differences have not been illuminated. In this study, a 15N tracing method was used to compare nitrogen use efficiency among six genotypes. The results show that there were significant differences in the NUEs among these genotypes. Among them, TC12 had the highest NUE, while LJCY had the lowest NUE. Transcriptome analysis between these two cultivars showed that differentially expressed genes (DEGs) were significantly enriched in photosynthesis—antenna proteins and zeatin biosynthesis in mature leaves and new shoots, respectively. TC12 had higher expression levels of AMT1.2, NRT2.4, and NRT3.2 in the roots, AAP6 and AAP7 in the stems and shoots, and LHC in the mature leaves than LJCY. The expression of ZOG1 and CKX, which are involved in zeatin biosynthesis, was down-regulated in the shoots of TC12 compared with LJCY. These findings will contribute to insights into the molecular mechanism of nitrogen utilization and the identified candidate genes provide a genetic resource for improving N use efficiency in tea plants.